(untitled) (Biological Sciences - PJSIR, 2004)
The herbicidal potentials of extracts derived from maize inflorescence were collected at 48, 96, 144, 196 and 240 h after formation were examined on the weeds, Siam-weed (Chromolaena odorata), Node-weed (Synedrella nodiflora) and Tridax ( Tridax procumbens). Two sets of aqueous extracts (A and B) were prepared. Treatment A involved the dispersion of the powdered extracts from the inflorescence in distilled water, while treatment B involved the addition of sodium chloride to the dispersed powder in distilled water. The extracts inhibited growth of the seeds of the weeds used when compared to the control. In both treatments 48 h extract tends to be the most effective. The effectiveness of the extracts decreases with an increase in the age of the inflorescence. Hence, more extract-treated seeds germinate with an increase in the age of the inflorescence. The addition of sodium chloride to the extracts tends to increase the potency of the extracts in delaying germination of weed seeds.